2010
DOI: 10.1249/mss.0b013e3181c0ea8c
|View full text |Cite
|
Sign up to set email alerts
|

Fitness and Exercise as Correlates of Sleep Complaints

Abstract: For early adulthood, findings did not support commonplace or expert opinion that exercise behavior has a favorable influence on sleep. Rather, the findings lend support to the importance of cognitive processes in the onset and maintenance of sleep complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 31 publications
(39 reference statements)
3
68
0
1
Order By: Relevance
“…On the other hand, previous studies have reported that aerobic exercise done in the form of running on a treadmill follows reduced levels of anxiety, stress, and depression resulting in improved sleep quality [31][32][33] . In addition, Yoga exercises were carried out for 90 min per session, while aerobic exercises lasted 35 min in the longest session.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, previous studies have reported that aerobic exercise done in the form of running on a treadmill follows reduced levels of anxiety, stress, and depression resulting in improved sleep quality [31][32][33] . In addition, Yoga exercises were carried out for 90 min per session, while aerobic exercises lasted 35 min in the longest session.…”
Section: Discussionmentioning
confidence: 96%
“…Gerber, Brand, Holsboer-Trachsler, and Pühse (2010) evaluated the relationship between exercise and sleep. The quantitative study included a sample size of 862 students from Switzerland.…”
Section: Exercise Habitsmentioning
confidence: 99%
“…The purpose of the study was to determine "if a person's perceived physical fitness, the level of exercise, and perceived lack of physical activity were associated with insomnia, dysfunctional sleep-related thoughts, and quality of sleep among young adults" (Gerber et al, 2010, p. 894). This study assessed the quality of sleep by measuring the students' difficulty falling asleep, difficulty maintaining sleep, waking up early, sleepiness during the day, low daytime performance, low satisfaction with sleep, and worrying about sleep (Gerber et al, 2010). Gerber et al (2010) found that there was a high correlation between sleep disturbances and physical inactivity.…”
Section: Exercise Habitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical conditions included cognitive processes, metabolic function, immune function, and appetite regulation while disruption of mood, decision-making and concentration were psychological conditions [8]. These conditions are interdependent and become a cycle as regular physical activity can improve sleep quality and good sleep quality enhances physical performance [9]. Therefore, adequate sleep can boost up athletes' performance and enhance learning.…”
Section: Introductionmentioning
confidence: 99%